Study of the Effect of Volume of Moringa Leaves and Purple Sweet Potato Extracts as a Green Corrosion Inhibitor on the Corrosion of API 5L Steel Metals in 0.2 M HCl Environments - Kezia; Yudha Pratesa; Tio Angger Pertama; Johny Wahyuadi Soedarsono (Recent in Engineering Science and Technology, 2025)
This study aimed to investigate the corrosion inhibition mechanism of moringa leaves extract (Moringa oleifera) and purple sweet potato extract (Ipomoea batatas) extract as environmentally friendly inhibitors for low carbon API 5L steel in a 0.2 M HCl solution. Potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) tests were conducted with varying concentrations and combinations of the two inhibitors to evaluate their corrosion inhibition performance. The results indicated that both inhibitors individually function effectively as green corrosion inhibitors. However, their combination did not offer adequate protection for API 5L steel in a 0.2 M HCl environment. FTIR analysis of the inhibitors confirmed the presence of flavonoid compounds in both extracts. Potentiodynamic polarization tests showed that increasing the concentration of moringa leaves extract resulted in a decrease in the corrosion rate and an increase in %IE, with the highest efficiency reaching 73.08%. Similarly, an increase in the volume of purple sweet potato extract also resulted in a reduced corrosion rate, with a maximum inhibition efficiency of 65.31%. However, the combination of both inhibitors led to an increase in the corrosion rate. The results of the EIS test demonstrated that both inhibitors protect the metal by forming a protective film layer on its surface. The adsorption behavior of the inhibitors corresponds to a physical adsorption process and aligns with the Langmuir adsorption isotherm model.